If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -6x = 7x + 15 Reorder the terms: -3 + -6x = 15 + 7x Solving -3 + -6x = 15 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -3 + -6x + -7x = 15 + 7x + -7x Combine like terms: -6x + -7x = -13x -3 + -13x = 15 + 7x + -7x Combine like terms: 7x + -7x = 0 -3 + -13x = 15 + 0 -3 + -13x = 15 Add '3' to each side of the equation. -3 + 3 + -13x = 15 + 3 Combine like terms: -3 + 3 = 0 0 + -13x = 15 + 3 -13x = 15 + 3 Combine like terms: 15 + 3 = 18 -13x = 18 Divide each side by '-13'. x = -1.384615385 Simplifying x = -1.384615385
| 9x+5=9x+13 | | 5(m+3)=2m+48 | | 3(5x+4)=18-6 | | 3(15x+4)=18-6 | | 6x^2-6x=12 | | 5x^2-10x+5= | | xa=ba+c | | ln(x-1)=0 | | bx+c=ax | | 7x^3=0 | | =4x-2x+y+6y | | 3x^2+27-30=0 | | 2a-4=132 | | 1x^2-12x+36=0 | | x(x^2)=0 | | x^2+576=10x | | x^2+576=10x^2 | | x+24=10x^2 | | x-x=y | | x-3=y | | 96-5x=7x+54 | | 19x^2+19x+12=0 | | -6w=-8 | | x^2=4x+4+100 | | 4y=256 | | 3y-1=(10y-18)/2 | | (3y-1)/2=(10-18) | | (3y-1)=2(10-18) | | 2(3y-1)=10-18 | | (8x-3)=3(5x+6) | | 3(8x-3)=5x+6 | | 8k-6k+3k= |